The Characteristics, Swelling Ratio and Water Content Percentage of Chitosan-gelatin/limestone-based Carbonate Hydroxyapatite Composite Scaffold - Rianti, Devi; Fanny, Geo; Nathania, Rania Vivian; Purnamasari, Alqomariyah Eka; Putri, Rifayinqa Ruyani; Soekartono, Helal; Soebagio; Yuliati, Anita; Syahrom, Ardiyansyah (International Journal of Integrated Engineering, 2022)
Background: The tissue engineering field has developed a scaffold that can be used to increase the bone regeneration process. Carbonate hydroxyapatite (CHA) is a well-known scaffold due to its components resembling human bones. Methods: The scaffold was synthesized from K, G, and limestone-based CHA using a freeze-drying method with K-G/CHA ratios (w/w) of 40:60, 30:70, 20:80, and 10:90. A Fourier transform infrared spectroscopy (FTIR), a scanning electron microscope-energy dispersive X-ray (SEM-EDX), and X-ray diffraction (XRD) were used to characterize the scaffold. Results: The FTIR test showed some functional groups, such as hydroxyl, amide I, amide II, carbonate, and phosphate. The SEM-EDX test showed micropore (50 um) structures as well as elements of C, N, O, Mg, Al, Si, P, and Ca. The XRD analysis obtained crystalline and amorphous particles. The WCP values obtained were 61.29%, 64.30%, 67.71%, and 67.78%. Conclusion: K-G/CHA composite scaffold with a ratio of 30:70 has ideal characteristics, a swelling ratio, and a WCP.